1990
DOI: 10.1002/jcla.1860040107
|View full text |Cite
|
Sign up to set email alerts
|

Human psychoneuroimmunology today

Abstract: Studies in human psychoneuroimmunology began around 1919, but a systematic approach wasn't used until the work of Solomon in the 1960s. Recently, the new specialty has achieved relative independence due to considerable data acquisition. Stress research has revealed relationships between neuroendocrine and immune changes. In parallel, increasing evidence of immunological alterations in psychiatric diseases has expanded the field; presently, immunological correlates of psychosomatic diseases and personality are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
3

Year Published

1992
1992
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 216 publications
(160 reference statements)
0
10
0
3
Order By: Relevance
“…However, the immune pa rameters we investigated are among the most commonly assessed in human psychoimmunological studies [37], A third limitation con cerns the restricted size of the sample. Several studies have already shown significant changes in immune functions after severe life stress [6,9,37], A larger sample could proba bly increase the possibility of detecting changes related to severe or important life events, and thus our results need to be repli cated with a larger sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the immune pa rameters we investigated are among the most commonly assessed in human psychoimmunological studies [37], A third limitation con cerns the restricted size of the sample. Several studies have already shown significant changes in immune functions after severe life stress [6,9,37], A larger sample could proba bly increase the possibility of detecting changes related to severe or important life events, and thus our results need to be repli cated with a larger sample.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a variety of studies have at tempted to assess the impact of stress on immune [3][4][5] and endocrine [6,7] system function by either correlating ratings of life stress with immune and endocrine physiology [8,9], or by sampling blood from volunteers before and after predictable stressors, such as examinations [10,11], preoperative stress [12], divorce [13], death of the spouse [14], conditioning procedures [15][16][17][18][19], and others [20,21]. On the whole, these studies demon strated stress-related changes in immune and endocrine system function, including de creased natural killer (NK) cell activity and decreased lymphocyte responses to the mito gens phytohemagglutinin (PHA) and concanavalin A (Con A), increased plasma cortisol, adrenocorticotropin (ACTH) and growth hor mone (GH) levels.…”
Section: Introductionmentioning
confidence: 99%
“…Sterilized food (Ultrasorb, PANLAB, Barcelona, Spain) and water were given ad libitum. Chronic injection of drugs may induce stressassociated effects on immunity and cancer (Riley 1975(Riley , 1981Biondi and Kotzalidis 1990). In our previous studies, we demonstrated that stress induced by the daily injection of placebo was enough to enhance MTV-induced tumor development (Freire-Garabal et al 1991).…”
Section: Mtv-induced Tumorsmentioning
confidence: 97%
“…Moderate chronic or intermittent stress may predispose such mice to an increased risk of mammary carcinoma, possibly through a resultant compromise of their immunological competence or tumor surveillance system, whereas adequate protection from physiological stress may reduce mammary tumor occurrence in mice (Riley 1975(Riley , 1981. Handling, capturing, and daily administration of drugs may induce stress-associated effects on immunity and cancer (Riley 1975(Riley , 1981Biondi and Kotzalidis 1990).…”
Section: Introductionmentioning
confidence: 98%
“…Linear models of symptom formation should thus be replaced by biopsychosocial or multifactorial models, focusing not on issues of specific aetiology, but on dynamic interactional processes involving predisposing, triggering and buffering factors [36]. The issue is further complicated by the fact that the stress reaction involves many equilibrium-stabilising mechanisms interacting at the level of cardinal physiological systems such as the neuroimmune system [37], the neuroendocrine system [38]and the neuromuscular system.…”
Section: Discussionmentioning
confidence: 99%